La franquicia, estrategia competitiva de desarrollo empresarial - Valdés Navarrete, Vilma (Libre Empresa, 2010)
Franchising is an excellent competitive strategy as it allows increasing participation in new markets without generating higher costs within firms. The world of franchising is based on an exciting and dynamic system that brings together the strengths of the business world and constitutes one of the fundamental pillars of economic growth, also offers many opportunities and benefits to both franchisors and franchisees, but also involves a series of obligations and legal and economic tradeoffs for both sides. Colombia is in a stage of growth strengthened markedly in recent years and reflected in several economic sectors such as apparel, snack foods, footwear, leather goods, services and general and specialized stores [1]. In this paper we analyze in detail the obligations of both parties to determine what advantages and disadvantages, and the contribution of the franchise business growth and development in Colombia